Impact of neonicotinoid seed treatment of cotton on the cotton leafhopper, Amrasca devastans(Hemiptera: Cicadellidae), and its natural enemies - Saeed, Rabia; Razaq, Muhammad; Hardy, Ian C.W. (Wiley, 2016)
BACKGROUND Neonicotinoid seed treatments suppress populations of pest insects efficiently and can enhance crop growth, but they may have negative effects on beneficial arthropods. We evaluated the effects of either imidacloprid or thiamethoxam on the abundances of a sucking pest, the cotton leafhopper (Amrasca devastans), and its arthropod predators under field conditions. We also evaluated the impact of seed treatment on transgenic cotton plant growth, with pests and natural enemies present or absent. RESULTS Imidacloprid and thiamethoxam reduced pest abundance, with greater effects when dosages were higher. Treatment at recommended doses delayed the pest in reaching the economic damage threshold by around 10–15 days (thiamethoxam) and 20 days (imidacloprid). Recommended doses also enhanced plant growth under all tested conditions; growth is affected directly as well as via pest suppression. Neonicotinoid applications reduced abundance of beneficial arthropods, with lower populations after higher doses, but negative effects of imidacloprid were not apparent unless the manufacturer-recommended dose was exceeded. CONCLUSION Imidacloprid applied at the recommended dose of 5 g kg−1 seed is effective against A. devastans and appears to be safer than thiamethoxam for natural enemies, and also enhances plant growth directly. We caution, however, that possible sublethal negative effects on individual beneficial arthropods were not evaluated.